Advanced real time imaging II : cutting-edge techniques in materials science studies ([Pittsburgh, PA] : TMS, 2019)
"Real time" imaging techniques have assisted materials science studies especially for non-ambient environments. These techniques have never been collectively featured in a single venue. The book is an assembly of materials studies utilizing cutting edge real time imaging techniques, emphasizing the significance and impact of those techniques.
También disponible en EPUB